The Influence of Leadership Style on Employee Performance - Haryadi, Imam; Bahiroh, Eloh (PT FORMOSA CENDEKIA GLOBAL, 2024)
Leadership can be said to be the key to the success of a company. With leadership in a company, the company will run in a structured manner and its employees will be well managed. The importance of leadership style in a company to be effective in achieving goals and remaining relevant in a changing environment. Leadership style in a company can determine how productive employees in a company are. The purpose of writing this journal is to analyze, find out, confirm whether there really is an influence of leadership style on employee performance. The writing method uses a qualitative descriptive method with techniques for searching, collecting and analyzing existing data. The results of the research show that leadership style can make employees enthusiastic and motivated to work.